Oxidative stress versus inflammation, a better predictor of cardiovascular disease risk in polycystic ovary syndrome - Sundharan, Shimi M.; Dipnaik, Kavita A.; Ingale, Pramod W.; Shelke, Sudarshan N.; Rai, Pooja S. K. (International Journal of Research in Medical Sciences, 2016)
Background: Polycystic ovary syndrome (PCOS) is also known as hyperandrogenic anovulation (HA) or Stein-Leventhal syndrome. PCOS has a diverse range of causes that are not entirely understood, but there is evidence that it is largely a genetic disease. Aim of the study was to evaluate better predictor of cardiovascular disease risk in women with polycystic ovary syndrome. Methods: 50 diagnosed patients of PCOS and 50 age matched healthy females were included in this study. Cases were diagnosed based on new Rotterdam criteria formulated by the American Society for Reproductive Medicine (ASRM). Fasting Blood samples were collected. Serum High sensitivity-C reactive protein (hs-CRP) and Malondialdehyde (MDA) were estimated. Results: Results were analyzed using unpaired t-test and p-value was calculated. Statistically non-significant increased levels of serum hs-CRP in PCOS cases as compared with controls were observed. MDA was found to be significantly increased in cases as compared to controls. ROC curve analysis shows MDA as a more specific predictor of cardiovascular disease risk in PCOS compared to hs-CRP. Conclusions: Increase in the serum MDA level indicates increased formation of reactive oxygen species and lipid peroxidation which leads to increased oxidative stress and this may increase cardiovascular disease risk in PCOS. hs-CRP a marker of chronic inflammation was not significantly increased in PCOS.